Changes in cardiac structure and function from 3 to 12 months after hospitalization for COVID‐19. Issue 10 (3rd August 2022) - Øvrebotten, Tarjei; Myhre, Peder; Grimsmo, Jostein; Mecinaj, Albulena; Trebinjac, Divna; Nossen, Magnus B.; Andrup, Simon; Josefsen, Tony; Einvik, Gunnar; Stavem, Knut; Omland, Torbjørn; Ingul, Charlotte B.
Abstract: Background: Cardiac function may be impaired during and early after hospitalization for COVID‐19, but little is known about the progression of cardiac dysfunction and the association with postacute COVID syndrome (PACS). Methods: In a multicenter prospective cohort study, patients who had been hospitalized with COVID‐19 were enrolled and comprehensive echocardiography was performed 3 and 12 months after discharge. Twenty‐four‐hour electrocardiogram (ECG) was performed at 3 and 12 months in patients with arrhythmias at 3 months. Results: In total, 182 participants attended the 3 and 12 months visits (age 58 ± 14 years, 59% male, body mass index 28.2 ± 4.2 kg/m 2 ). Of these, 35 (20%) had severe COVID‐19 (treatment in the intensive care unit) and 74 (52%) had self‐reported dyspnea at 3 months. From 3 to 12 months there were no significant overall changes in any measures of left or right ventricle (LV; RV) structure and function ( p > .05 for all), including RV strain (from 26.2 ± 3.9% to 26.5 ± 3.1%, p = .29) and LV global longitudinal strain (from 19.2 ± 2.3% to 19.3 ± 2.3%, p = .64). Changes in echocardiographic parameters from 3 to 12 months did not differ by COVID‐19 severity or by the presence of persistent dyspnea ( p > .05 for all). Among patients with arrhythmia at 3 months, there was no significant change in arrhythmia burden to 12 months. Conclusion: Following COVID‐19, cardiac structure and function remained unchanged from 3 to 12 months after the index hospitalization, irrespective of COVID‐19 severity and presence of persistent dyspnea. These results suggest that progression of cardiac dysfunction after COVID‐19 is rare and unlikely to play an important role in PACS.